Road user handbook - Transport for NSW (Auburn, NSW : Transport for NSW., 1992)
"The Road User Handbook covers the main rules you need to know to drive legally and safely on NSW roads. It's essential reading for anyone learning to drive. It aims to prepare you for the challenges of driving and reduce your risk on the road." -- Introduction.
Includes index.
Formerly available in print (until <2009?>).
Mode of access: Available online.
Also issued in various other languages.
Description based on: Pub. 20.208 (2021); title from title screen
Keywords: Motor vehicle driving -- Australia -- New South Wales -- Handbooks, manuals, etc; Motor vehicle driving -- Australia -- New South Wales -- Handbooks, manuals, etc; Motor vehicle driving -- New South Wales -- Handbooks, manuals, etc; Traffic safety -- Australia -- New South Wales -- Handbooks, manuals, etc; Traffic safety -- Australia -- New South Wales -- Handbooks, manuals, etc; Traffic safety -- New South Wales -- Handbooks, manuals, etc; Motor vehicle driving; Traffic safety; New South Wales; Electronic journals; Periodical; Periodicals; Periodicals